2018
DOI: 10.1016/j.clgc.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Levels of 4EBP1/eIF4E Activation in Renal Cell Carcinoma Could Differentially Predict Its Early and Late Recurrence

Abstract: A subset of patients who undergo curative surgery for localized clear cell renal cell carcinoma (ccRCC) will experience early or late recurrence. Tumor viability depends on protein synthesis via the eukaryotic initiation factor (eIF)4E-binding protein 1 (4EBP1/eIF4E) axis. Activation levels of the axis in ccRCC tissues could differentially affect tumor recurrence and the timing of recurrence after curative nephrectomy. Background: The objective was to explore the predictive markers of late recurrence (LR) > 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Conversely, MNK2 selectively interacts with mTORC1 in a kinaseindependent manner and inhibits S6K phosphorylation [25]. Recently, we demonstrated that the lower or higher expression of eIF4E reflected a weaker or stronger activation of the mTORC1/4EBP1/eIF4E signalling pathway, respectively [26]. In the present study, significantly lower eIF4E and higher p-eIF4E expressions were observed in ccRCC patients who did not experience tumour recurrence than in those who did.…”
Section: Discussionsupporting
confidence: 58%
“…Conversely, MNK2 selectively interacts with mTORC1 in a kinaseindependent manner and inhibits S6K phosphorylation [25]. Recently, we demonstrated that the lower or higher expression of eIF4E reflected a weaker or stronger activation of the mTORC1/4EBP1/eIF4E signalling pathway, respectively [26]. In the present study, significantly lower eIF4E and higher p-eIF4E expressions were observed in ccRCC patients who did not experience tumour recurrence than in those who did.…”
Section: Discussionsupporting
confidence: 58%
“…One supposed reason for the result is that phosphorylation of 4EBP1 promotes to dissociate 4EBP1/eIF4E assembly (7,8). Actually, we previously elucidated that high levels of 4EBP1/eIF4E activation predicts RCC recurrence (14). Another reason is the consequence of Akt/mTORC1 pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Akt activation by low-density lipoprotein (LDL) addition in RCC cell lines counteracts the anti-tumor effects of the VEGF-targeted agents sunitinib and sorafenib (13). In adition, we have previously reported that high levels of 4EBP1/eIF4E activeation predict higher recurrence rate (14).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia and necrosis determined as significant radiomic features played a central role in RCC progression by modulating critical signaling pathways including PI3K/AKT signaling, Notch signaling, Wnt signaling, and focal adhesion, governing stem-cell-like phenotype, cancer cell plasticity, metabolic reprogramming, epithelial-to-mesenchymal transition (EMT) closely associated with higher probability to escape the primary tumor and survive in an avascular metastatic site [2,5,21,[38][39][40]. The aberrant overexpression of key proteins via cap-dependent mRNA translation is known to be a requisite for tumor progression and metastasis via the strong activation of the eukaryotic initiation factor (eIF) 4E-binding protein 1 (4EBP1/eIF4E) axis in RCC [41]. Furthermore, an ECM remodeling program and an ECM-receptor interaction pathway facilitate cell survival, angiogenesis, EMT, and metastasis of RCC via the subsequent activation of the focal adhesion kinase (FAK)/c-Jun N-terminal kinase pathway and PI3K/AKT pathway [42][43][44].…”
Section: Discussionmentioning
confidence: 99%